Numerical analysis of the soil deformation caused by tunneling under vehicle loads in the coastal reclamation area - Zou, Baoping (2015)
Prediction of tunneling induced soil deformation is an important issue in the design of tunnels constructed in the densely populated urban areas. In this paper, commercial FEM software 3D ABAQUS is adopted to simulate the behavior of soil caused by tunneling under vehicle loads in the coastal reclamation area. A field case study was also carried out to verify the accuracy of the proposed model. A good agreement was achieved. It is also found from the studies that the areas affected by soil deformation can be classified into four zones: the key disturbed zone, the secondary disturbed zone, the general disturbed zone, and minor-disturbed zone. The maximum soil deformation occurs on side of the longitudinal medial axis of the tunnel. The shape of the settlement curve is almost the same as that of the normal distribution curve. The soil deformation in the action zone of vehicle load is greater than that of the nonaction zone of vehicle load.